MODEL KOLABORATIF PENGKAJIAN RISIKO BENCANA BANJIR LAHAR SUNGAI TUGURARA KOTA TERNATE - , MUHAMMAD RIZKI SATRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lava floods Tugurara river is the secondary hazard from Gamalama mount eruption happened in Mei 2012 has an impact to 3 villages: Tubo villages, Akehuda Villages, and Dufa-dufa villages. Many people was affected by natural disaster . collaborative model of lava flood risk assessment is a combine methods of existing (BNPB Regulation number 2 2012) and community based that involved in risk assessment. The aim of this research is to implement collaborative model of risk assessment in Ternate City